Pengaruh Kepercayaan Konsumen, Kualitas Pelayanan, dan Celebrity Endorsement terhadap Keputusan Pembelian pada Marketplace Shopee - Mutiara Nur Azizah; Muzakar Isa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study was to analyze the effect of consumer trust, service quality, and celebrity endorsement on purchasing decisions in the shopee marketplace. This research method uses quantitative. The population in this study were shopee marketplace users in Solo Raya. This study uses sampling with Non-probability Sampling techniques with a Purposive Sampling approach because the population in this study is not known with certainty. The number of samples in this study were 100 respondents. The data used in this research is primary data. The data collection methods used in this research are questionnaires and research instruments. The data analysis technique in this study used SmartPLS software version 3.2. The results of this study are that consumer confidence has a positive and significant effect on purchasing decisions in the shoope marketplace. The quality of service provided has no positive and significant effect on purchasing decisions. Celebrity Endorsement has a positive and significant effect on purchasing decisions.